Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd007102.pub3
|View full text |Cite
|
Sign up to set email alerts
|

First-line chemotherapy in low-risk gestational trophoblastic neoplasia

Abstract: Dactinomycin is more likely to achieve a primary cure in women with low-risk GTN, and less likely to result in treatment failure, compared with methotrexate. There is limited evidence relating to side-effects, however, the pulsed dactinomycin regimen does not appear to be associated with significantly more side-effects than the low-dose methotrexate regimen and therefore should compare favourably to the five- and eight-day methotrexate regimens in this regard.We consider pulsed dactinomycin to have a better cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Many different schedules have been devised, all of which seem to have activity, but comparison of results is hampered by differences in patient inclusion criteria among other issues. 21 In Europe and many centers internationally, MTX/FA (Table 3) is preferred because it is less toxic. Thus, unlike ActD, it causes no hair loss, induces less nausea and vomiting, and is less myelosuppressive.…”
Section: Table 1 Indications For Chemotherapy After a Molar Pregnancymentioning
confidence: 99%
“…Many different schedules have been devised, all of which seem to have activity, but comparison of results is hampered by differences in patient inclusion criteria among other issues. 21 In Europe and many centers internationally, MTX/FA (Table 3) is preferred because it is less toxic. Thus, unlike ActD, it causes no hair loss, induces less nausea and vomiting, and is less myelosuppressive.…”
Section: Table 1 Indications For Chemotherapy After a Molar Pregnancymentioning
confidence: 99%
“…There is little consensus worldwide as to the optimal agent and regimen, although methotrexate is favored. 1 Dactinomycin is generally reserved for use as a second-line salvage therapy as it has historically been associated with more severe toxicity. 1,6 Several randomized trials have suggested that dactinomycin is associated with higher complete response rates than methotrexate, without an increase in toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 Several randomized trials have suggested that dactinomycin is associated with higher complete response rates than methotrexate, without an increase in toxicity. 1 However, these have been criticized as being underpowered, comparing protocols that are not commonly used worldwide, as well as using weekly methotrexate protocols, which are generally considered less effective than alternate protocols. 7,8 Complete response rates for methotrexate alone are reported between 50% and 85%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment is usually continued until either normalization of serum human chorionic gonadotrophin (hCG) concentration followed by 1 to 3 additional cycles or resistance to this drug is detected. 1,2 Tumor chemoresistance is frequently characterized as an increase or stagnation of hCG levels during a 2-to 3-week period, but no consensus guideline has been defined. 3 An early assessment of single-agent resistance risk is desirable because it may reduce the likelihood that patients will receive repetitive ineffective chemotherapy cycles.…”
mentioning
confidence: 99%